The Meaning of the Lyrics of Gorontalo Regional Songs in Rizky Onefyt's Album: A Semiotic Study by Roland Barthes - Nurhalima Mangilo; Ellyana Hinta; Wa Ode Irawati (Raja Zulkarnain Education Foundation, 2026)
This research is motivated by the declining interest of the younger generation in regional songs due to the dominance of popular music in the digital space, which has resulted in a diminished understanding of local cultural values. Gorontalo regional songs serve not only as entertainment but also as a medium for transmitting values, identity, and the community’s outlook on life. This study aims to describe the representation of Gorontaloan life in song lyrics and uncover their meanings through a semiotic study. This study uses a descriptive method with a Roland Barthes semiotic approach. The research data consists of song lyrics from Rizky Onefyt’s Gorontalo folk song album. The data were collected through reading and note-taking techniques, then analyzed by identifying signifiers and signifieds, and examining meaning at three levels: denotation, connotation, and myth. The research results show that at the denotative level, song lyrics represent the concrete realities of Gorontalo society, such as places, activities, and events. At the connotative level, meaning develops into emotional and cultural representations, such as longing, togetherness, conflict, and social relationships. At the mythical level, song lyrics reproduce naturalized social values, such as identity, loyalty, sacrifice, social roles, and views on life and migration. The lyrics of Gorontalo regional songs in Rizky Onefyt’s album serve not only as aesthetic expression but also as a representation of the socio-cultural life and ideology of the community. This research is expected to contribute to literary and cultural studies and support the preservation of regional songs as a form of local cultural identity.